Evaluation Criteria to Assess Gender and Social Inclusion in AICCRA Kenya - Bullock, Renee (Accelerating Impacts of CGIAR Climate Research for Africa, 2021)
Evaluation Criteria to Assess Gender and Social Inclusion in agricultural and pastoral development interventions